Case report: A rare case of massive peripheral nerve melanotic schwannoma and review of the literature - Wang, Han; Shi, Lin; Tian, Tong; Xian, Hang; Song, Zhao; Cong, Rui; Zhao, Rui (Frontiers in Neurology, 2023)
Melanotic schwannoma is a rare tumor with indeterminate biologic behavior and varying treatment recommendations. Just about 200 cases have been reported worldwide, in which occurred in peripheral nerves has even less reported. Due to the lack of cognition of melanotic schwannoma, it is easy to be misdiagnosed and mistreatment in primary hospitals. Herein, we presented a case of massive melanotic schwannoma growing in the brachial plexus of an elderly male patient. First, the patient underwent a left forearm tumor resection in the local primary hospital because a painless lump was found there in 2017, of which details remain unclear. After this operation, the patient developed the symptoms of left median nerve injury. Thus, he came to our hospital and underwent a second operation. During this operation, we found that a part of the median nerve was absent at the left forearm, and the remanent median nerve, from the broken end to the elbow, was totally turned black, which was accompanied by petroleum-like exudate. Losing the opportunity for nerve repair, the black nerve was removed extensively and thoroughly. Postoperative pathological diagnosis revealed that the tumor was melanotic schwannoma. Then 4 years later, the tumor recurrence again, which led to the paralysis of the whole left arm and severe nerve pain, and the pulmonary metastasis of the tumor was detected at the same time. The black nerve was resected again in our hospital, and the nerve pain was partially relieved after the operation. To the best of our knowledge, it is the first time to report a melanotic schwannoma case that happened in the peripheral nerve trunk and then spread to the whole brachial plexus. There were many questions that worthy of discussion could be invited from this case, and we analyzed and discussed them based on the relevant literature. In conclusion, we reported a rare case of melanotic schwannoma that happened in the brachial plexus and illustrated the problems of the diagnosis and treatment of it based on the analysis of the relevant literature, which is helpful for the cognition of this rare nerve tumor.